2015
DOI: 10.1166/jnn.2015.10227
|View full text |Cite
|
Sign up to set email alerts
|

A Resultant Stress Effect of Contact Etching Stop Layer and Geometrical Designs of Poly Gate on Nanoscaled nMOSFETs with a Si<SUB>1−x</SUB>Ge<SUB>x</SUB> Channel

Abstract: In this research, an n-type metal-oxide-semiconductor field effect transistor (nMOSFET) device with a SiGe channel exerted by the combination of a contact etching stop layer (CESL) and silicon germanium (Si1-xGe(x)) channel stressors is proposed. To explore the foregoing mechanical effect on the stress distribution of nMOSFETs within the channel region, a process-oriented simulated technique is adopted for the concerned nMOSFET device. The loading sources are a 1.1 GPa tensile CESL (t-CESL) and a SiGe channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Recently, more and more articles pay attention on nanoscale Ge or GeSi MOSFET. Both the experimental and simulation work presented the stress-induced mobility gain of CESL as strongly dependent on the layout arrangement of devices, particularly in situations with narrow widths [ 186 ]. P. Nguyen et al has demonstrated induced CESL in Ω-gate CMOS nanowires with p-FETs and n-FETs down to W = 15~20nm gate length [ 187 , 188 ].…”
Section: Sin X Film and Strain Engineeringmentioning
confidence: 99%
“…Recently, more and more articles pay attention on nanoscale Ge or GeSi MOSFET. Both the experimental and simulation work presented the stress-induced mobility gain of CESL as strongly dependent on the layout arrangement of devices, particularly in situations with narrow widths [ 186 ]. P. Nguyen et al has demonstrated induced CESL in Ω-gate CMOS nanowires with p-FETs and n-FETs down to W = 15~20nm gate length [ 187 , 188 ].…”
Section: Sin X Film and Strain Engineeringmentioning
confidence: 99%